Tooth Crown Size of the Permanent Dentition in Subjects with Thalassemia Major - F. H. Hattab; E. S. J. Abu-Alhaija; O. M. Yassin (Dental Anthropology Association, 2000)
Thalassemia refers to a group of hereditary anemias resulting from defects in synthesis of either alpha or the beta polypeptide chains of hemoglobin. The homozygous form of beta thalassemia (thalassemia major) exhibits the most severe clinical symptoms. Odontometric analysis of subjects with thalassemia are lacking, despite the wide distribution of the disease and its orofacial characteristics. The aim of this study was to provide detailed descriptions of tooth crown size in the permanent dentition of subjects with thalassemia major and to compare the findings with those of the same population. Dental casts of 46 thalassemic subjects, 25 males and 21 females, aged 7.3 to 23.7 years, were measured for the mesiodistal and buccolingual crown diameters. Crown size variability, correlations, sexual dimorphism, and summary measurements are presented. All means for mesiodistal and buccolingual dimensions in males exceeded those in females, with 18 of the 28 comparisons statistically significant (ranged from P<0.05 to P<0.001, t-test). With the exception of maxillary central and lateral incisors and mandibular first molars, all other teeth exhibited greater buccolingual diameters than mesiodstal. No specific pattern of percentages of sexual dimorphism was noted between the mesiodistal and buccolingual diameters. Comparison of the mesiodistal crown diameters in thalassemic subjects with unaffected control group showed that thalassemic males and females have significantly smaller dimensions than their controls, with 9 of the 24 comparisons being highly significant.